Decolonizing Agrarian Knowledge and the Emergence of Indonesian Critical Agrarian Studies - Ahmad Nashih Luthfi (Universitas Gadjah Mada, 2020)
Agricultural production growth has been the main priority in agrarian development in Indonesia but its ends and means have been varied. In the colonial era, an export- oriented colonial plantation system resulted in the transformation of the Indonesian land tenurial system. In the post-colonial period, Soekarno’s regime pursued agrarian development seeking to strengthening people’s land rights through its land reform policies. Land rights were seen as the basis for agricultural production. Soeharto’s New Order regime implemented its Green Revolution policy by developing agricultural mechanization and extensification which managed to improve agricultural production, but it gave greater privileges to the rural elite class and caused dependence on foreign inputs and aid. All agrarian policies were supported by knowledge produced through the research of influential institutions and individuals, including critical responses against the impacts of the transformation of land tenure. In this context, knowledge in agrarian studies with its critical perspectives were re-shaped as part of the process of knowledge decolonization.